Переслідування та ліквідація УАПЦ (УПЦ) (1921–1938 рр.): огляд архівно-кримінальних справ ГДА СБ України та ЦДАГО України - Преловська, І. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
The present article analyzed the documents of criminal cases opened on main figures of Ukrainian Autocephalous Orthodox Church (Ukrainian Orthodox Church) that shed the light on the relationships between the state and the church in 1920th – 1930th as well as on the mechanism that launched the repression against the believers in Ukraine.